Implementation of Ngebel Lake Tourism Development as a Leading Natural Tourist Destination in Ponorogo District - Shakti, Titus Wirangga; Al Ghifari, Rifqi Putra; Fitri, Anisa Mamba'ul; Hardjati, Susi (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2024)
The tourism sector is a major contributor to the country